A institucionalização do movimento ambientalista: um estudo da formação do Partido Verde no Brasil - Santos, Adriana Vitória dos (2008)
The objective of this research is to analyze the political process that led to the creation of the Partido Verde ("Green Party") in Brazil. We have investigated what are the mechanisms that mobilize people around collective issues, specifically what are the motivations that led part of the environmentalist movement to opt for the creation of the party PV (Partido Verde) as a mobilization strategy. The research will focus on the political process and the negotiations around the creation of the PV in the 80s. Although the Brazilian party Partido Verde is mentioned in studies about environmentalist movements, it has never been the topic of any specific study. The creation of PV was not a unanimous decision among the diverse environmentalist groups. For this reason, we have deemed paramount a comparative analysis between the groups in São Paulo and Rio de Janeiro in order to understand their particularities. Thus, this study identified the reasons why the majority of the movement had engaged in the party in Rio and not in São Paulo. We will begin with the approach of the theory of political process (Tarrow, 1994) in order to explain the phenomenon, specially the concepts of "structure of political opportunities" and "structures of mobilization". Two research procedures were used: information gathering from archives of newspapers and magazines at that time; and semi-directive interviews with the main founders of PV and with the movement activists who were against that strategy. The first hypothesis examined was the importance of the redemocratization process, for which the country was going through from the 70 s to the 80 s, to promote new social movements and their later institutionalization. Besides the analysis of the political context, we have noticed relevant differences in the paths taken by the environmentalist groups and militants in São Paulo and in Rio de Janeiro. Therefore, a second hypothesis was identified related to the importance of an analysis on the formation of environmentalist groups to determine their view on the strategy to institutionalize the movement though a political party. As a result of the investigation, we demonstrate that the structure of national and regional opportunities stimulated the group of former exiles from Rio de Janeiro to create the Partido Verde in Brazil. Furthermore, the political militancy path previously taken by this group has also shown to be a motivation to bring the issue of the "partyzation" into the environmentalist movement